Note on the first historical records of two invasive plants in the Baja California peninsula: chronicle of the Jesuit missionary Miguel del Barco - Garcillán, Pedro P.; Rebman, Jon P. (Instituto de Ecología, A.C., 2016)
The date of introduction of invasive species in new areas is of high ecological, evolutionary and biogeographical relevance, although it can be difficult to determine. Historical sources on the European colonization period may contain relevant data about the arrival of some non-native taxa in America. During the Jesuit missionary period (1697-1768) in the Peninsula of Baja California (PBC), the first permanent human settlements were established and agriculture and livestock were introduced. Written sources by Jesuit missionaries who were present in the PBC were reviewed and precise data were found in the chronicle of Miguel del Barco regarding the presence and abundance of two currently invasive plants Arundo donax and Ricinus communis, which were already present in the PBC by the first half of eighteenth century.